Integrated transcriptomic and metabolomic analyses revealed the regulatory mechanism of sulfur application in grain yield and protein content in wheat (Triticum aestivum L.) - Liu, Zhilian; Liu, Dongcheng; Fu, Xiaoyi; Du, Xiong; Zhang, Yuechen; Zhen, Wenchao; Li, Shan; Yang, Haichuan; He, Suqin; Li, Ruiqi (Frontiers in Plant Science, 2022)
Sulfur fertilizer plays an important role in increasing the yield and improving the dough quality of bread wheat, but its regulatory mechanism remains unclear. In this study, 0 kilograms per hectare (kg·ha-1, S0) and 60 kg·ha-1 (S60) of sulfur were applied on the anthesis date; subsequently, immature wheat grains at 8, 13, and 18 days post-anthesis (DPA) were subjected to integrated transcriptomic and metabolomic analyses to investigate the changes in gene/metabolite activity in a typical strong-gluten wheat, Gaoyou2018 (GY2018). Our data show that the S60 treatment could significantly increase the grain yield and grain protein content by 13.2% and 3.6%, respectively. The transcriptomic analysis revealed that 10,694 differentially expressed genes (DEGs) were induced by S60 from 8 to 18 DPA compared to their corresponding no sulfur controls, and most DEGs were mainly involved in lipid metabolism and amino acid metabolism pathways. Ninety-seven MYB transcription factors (TFs) were identified as responsive to the S60 treatment; of these, 66 showed significantly differential expression at 13 DPA, and MYB118 might participate in the process of sulfur metabolism by regulating glucosinolate synthesis. In total, 542 significantly enriched differentially expressed (DE) metabolites (DEMs) were identified following the S60 treatment, which mainly included secondary metabolites, carbohydrates and amino acids. Several metabolites (e.g., glutathione, sucrose, GDP-alpha-D-glucose and amino acids) exhibited altered abundances following the S60 treatment. The combination of transcriptomic and metabolomic analyses highlighted the important role of amino acid metabolism (especially cysteine, methionine and glutathione metabolism) and starch and sucrose metabolism pathways after S60 application. Our results provide valuable information enhancing our understanding of the molecular mechanism of the response to sulfur and provide useful clues for grain protein quality formation and yield improvement in bread wheat.